SIMULATION AND ITS COMPONENTS - BISHT, RAHUL (International Journal of Current Pharmaceutical Research, 2022)
One of the most important steps in curriculum development is the introduction of simulation-based medical teaching and learning. Simulation is a generic term that refers to an artificial representation of a real-world process to achieve educational goals through experiential learning. Simulation based medical education is defined as any educational activity that utilizes simulation aides to replicate clinical scenarios. Although medical simulation is relatively new, simulation has been used for a long time in other high-risk professions such as aviation. Medical Simulation has been proven to reduce medical errors and the associated costs all while improving outcomes in patient care. While the use of simulation is mandated and regulated in aviation and many other high-performance industries, the methodology has yet to be required in healthcare [1].